History and future perspectives for the use of fluorescence visualization to detect oral squamous cell carcinoma and oral potentially malignant disorders - Tomo, Saygo [UNESP]; Miyahara, Glauco Issamu [UNESP]; Simonato, Luciana Estevam (Elsevier, 2019)
The early diagnosis of oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMD) is challenging. The use of fluorescence visualization (FV) has been improved as an auxiliary method to early detect alterations in the oral mucosa suggestive of malignancy or pre-malignancy. However, perhaps due to some misinterpretation regarding the clinical purpose of this method, its applicability may have been underestimated. The purpose of this review is to comment on the challenges within the prevention and early diagnosis of OSCC and OPMDs; to contextualize the use of fluorescence-based methods in the diagnosis of human cancers; and to critically analyze the methods and results of studies that evaluated the FV to detect OSCC and OPMDs, and how this method might be applicable in the clinical practice. The current evidence available in the scientific literature indicates that the FV has the potential to improve the early detection of OSCC and OPMDs. Its use in primary healthcare by general practice dentists, oral hygienists, and oral health therapists is recommended, although more research in the population screening scenario is still required.
Keywords: Autofluorescence; Optical fluorescence imaging; Oral cancer; Oral diagnosis; Oral potentially malignant disorders